A green approach for electromembrane extraction of morphine from urine using sodium alginate-g-polyacrylic acid/agarose hydrogel membrane - Elnaz Khodabakhshi; Somayeh Makarem; Mehran Kurdtabar; Saeed Nojavan (Advances in Sample Preparation)
The development of novel membranes through green chemistry remains a significant challenge in advancing practical separation science. In this study, a sodium alginate-g-polyacrylic acid/agarose hydrogel was synthesized and, for the first time, applied as a membrane in gel electromembrane extraction (G-EME) for the isolation of morphine, a basic analyte, from urine samples. The extracted morphine was subsequently quantified using differential pulse voltammetry (DPV) with a glassy carbon electrode. The hydrogel membrane (5 mm thick) was prepared using 0.75 % (w/v) sodium alginate, 3.80 % (v/v) acrylic acid, 0.04 % (w/v) ammonium persulfate, and 1.25 % (w/v) agarose. The extraction process was optimized by evaluating factors such as membrane composition, extraction time, applied voltage, and pHs of the sample solution, membrane, and acceptor phase (AP). Under optimal conditions (25 min extraction time, 70 V applied voltage, membrane pH 4.0, AP pH 3.0, and sample solution pH 7.0) morphine was efficiently extracted through the hydrogel membrane and transferred to an aqueous AP. The collected AP was mixed with 0.15 M phosphate buffer (pH 7.0) and analyzed voltammetrically. The method achieved a limit of detection of 0.09 μg/mL and a limit of quantification of 0.28 μg/mL, and was successfully applied for morphine determination in urine sample. The polyacrylic acid-based membrane enhanced extraction efficiency through electrostatic interactions, while the use of DPV offered clearer signal interpretation and reduced background current, facilitating reliable detection of trace analytes. These advantages support the method’s potential for simple, selective, and environmentally friendly analysis of basic drugs in biological samples.